Pengaruh Struktur Modal, Ukuran Perusahaan, Pertumbuhan Perusahaan dan Kinerja Keuangan Perusahaan Terhadap Nilai Perusahaan yang terdaftar di Jakarta Islamic Index(JII) periode 2010-2015 - Heningtyas, Oryza Sativa; , Dr. Zulfikar, SE, M.Si (2017)
ABSTRACT The value of the company is one of the main objectives of the company by way of maximizing shareholder value. There are several factors that affect the value of the company, but the authors only examined four variables, namely capital structure, company size, growth company corporate finance and general performance. This study aimed to examine the effect of capital structure (DER), firm size (Size), Growth Company (PTA), Corporate Financial Performance (ROA) to firm value (PBV) . Sampel this study is Manufacturing company registered in Jakarta Islamic Index ( JII) in the period 2010-2015 with a number of 10 companies by using purposive sampling method. The analytical method used is the classic assumption test and test hypotheses and multiple linear analysis. The results showed that the capital structure does not significantly influence the value of the company, the size of the company has a significant negative effect on the value of the company, the company's growth has no significant effect on firm value. The financial performance of the company have a significant effect on firm value. Keywords: capital structure, company size, growth, financial performance, the company's value.